On a class of autoresonant machines of vibro-impact action - Krupenin, V. L.; Myagkohlib, K.B. (Reports of the National Academy of Sciences of Ukraine, 2014)
The mechanism of organization of autoresonant vibro-impact technological machines is described. It involves a feedback loop, which includes the measurement of pulses hitting the working body, which is the integral of a conservative movement within the corresponding model. Examples and the calculation formulas are given. It is indicated that similar principles of organization of machines can be developed at the measurement of other integrals of motion.